Domestic english-language medical blog and its types - Черкащенко, Медея Рустамівна (Запоріжжя : Молодіжна наукова ліга, 2020)
With the onset of the 21st century, the rapid development of society's consciousness became noticeable, namely, the emergence of awareness. One of the impetus for this process was the development of information technology, the emergence of social networks, which gave people the opportunity to express their opinions, which they can hear, see, support or refute. Not so long ago, it became popular in society to run their own blogs on a variety of topics that have their supporters or opponents.